2008
DOI: 10.1007/s11150-008-9034-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation, income, and non-pecuniary economic outcomes: new evidence from young lesbians in Australia

Abstract: Sexual orientation, Economic outcomes, Australia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 23 publications
7
51
0
4
Order By: Relevance
“…Thus, it is not certain that any pecuniary advantage experienced by employees in the labour market could directly reflect or translate into more job satisfaction. In addition, Carpenter (2008) using the 2000…”
Section: Using the 2003 Canadian Communitymentioning
confidence: 99%
“…Thus, it is not certain that any pecuniary advantage experienced by employees in the labour market could directly reflect or translate into more job satisfaction. In addition, Carpenter (2008) using the 2000…”
Section: Using the 2003 Canadian Communitymentioning
confidence: 99%
“…6 Consistent with the idea that children are important reasons for formal unions and with the limited fertility of gay couples, Carpenter and Gates (2008) found in their study of homosexual Californians that lesbian couples 2 For the United States, see Allegretto and Arthur (2001), Badgett (1995Badgett ( , 2001, Black et al (2008), Carpenter (2004, Clain and Leppel (2001), and Klawitter and Flatt (1998). For Australia, see Carpenter (2008). For the UK, see Arabsheibani et al (2004Arabsheibani et al ( , 2005.…”
Section: Introductionmentioning
confidence: 95%
“…Carpenter (2008) investigated a representative sample of Australian women aged 18-23 in 1996. He found that lesbian women's prevalence of high school dropout and college completion was not significantly different from that of heterosexual women, but bisexual women were significantly overrepresented among high school dropouts compared to heterosexual women (there was no significant difference in college completion).…”
Section: Introductionmentioning
confidence: 99%